Deception of Meleney’s gangrene-saving from a potential mortality - Sunderraman, Shruthi; R, Guru Prasad; Muthuramalingam, Aravinth Ram; Sounderrajan, Harish; Rajendhiran, Rohini; Kathirvel, Senguttuvan (Indian Journal of Case Reports, 2026)
Meleney’s Gangrene is an acute, rapidly advancing polymicrobial infection of the anterior abdominal wall, often referred to as ‘flesh-eating disease. This condition is characterised by its unique etiology, a polymicrobial infection involving both aerobic and anaerobic organisms. What makes Meleney’s gangrene particularly dangerous is its deceptively slow progression in the initial phase, followed by a rapid, fulminant deterioration, often unresponsive to conventional wound care or empirical antibiotic therapy alone. In this case presentation, we report a 42-year-old patient who developed Meleney’s gangrene post-blunt trauma to the anterior abdominal wall. The case highlights the diagnostic challenges, clinical course, management approach, and outcome associated with this unusual but potentially fatal infection. The polymicrobial synergy makes surgical intervention and aggressive debridement essential. Broad-spectrum antibiotic therapy, guided by culture and sensitivity, forms a critical part of management, along with supportive care for sepsis.